Integration of a Constructivism Approach in E-learning Photography Subjects: Feasibility and Effectiveness in Learning - Kristanto, Andi (Universitas Pendidikan Ganesha, 2021)
Lack of lecture time was a serious problem and must be addressed immediately in the study of photography courses because of the large amount of material; the number of cameras is not comparable to that of students. Moreover, conventional learning through the face of the muka by using PowerPoint makes students bored and less interested in learning. This research aimed to develop e-learning with a constructive approach to photography subjects triangle exposure material and know the feasibility and effectiveness. This research was a type of research R &D (Research and Development )using the Addie model, Analyze, Design, Development, Implementation, and Evaluation. This study involved three validators, namely learning design experts, material experts, media experts and student motorcycle taxis, and there were control classes and experiments with a sample count of 80 students per class. The method of collecting data using questionnaire instruments and tests. Method analysis data using descriptive percentage and independent test t-test samples. The average assessment results of each expert's percentage were: (a) the assessment of learning design experts 96.66% of the excellent category; (b) material experts 95% excellent category; (c) media experts 95.58% excellent category, individual trials 84.05% excellent category, individual trials 88.37% excellent category. The effectiveness of constructivist e-learning with significant results in sig (2-tailed) column of 0.00 or significance of < 0.05. Based on the research results obtained, e-learning with a viable constructivist approach and effective implications used in lectures on photography courses.